Implementation of the Hierarchical Analytical Process in the Selection of the Best Source of Renewable Energy in the Colombian Caribbean Region - Moreno Rocha, Christian Manuel; Alvarez, Jose Ricardo Nunez; Castillo, Daniel A. Diaz; Domingue, Esnaider D. Florian; Hernandez, Juan Camilo Barrera (International Journal of Energy Economics and Policy, 2022)
In this study, the Analytic Hierarchy Process (AHP) methodology is implemented to provide decision criteria in the selection, planning, and development of electric power generation projects from renewable energy sources in the Caribbean region of Colombia. Six sources of renewable energy; biomass combustion; anaerobic digestion of biomass; biogas landfills; waste incineration; Photovoltaic energy and solar thermal radiation were considered in this study due to their energy potential in rural areas and areas not interconnected to the national electricity system. To determine the order of priority in the development of energy conversion technologies, a questionnaire was developed and sent to a group of experts. Given the need to generate electricity sustainably, the information was analyzed under four main criteria: technical, environmental, social, and economic. Sixteen additional sub-criteria were selected based on a literature review. In general, the economic criterion is the most relevant in the area due to the high investment and operating costs of electricity generation. The social criterion highlights the opportunity to create new jobs, while the environmental criterion highlights the component of substitution of renewable energy, a key aspect in the diversification of the energy matrix, which is part of the country's political agenda. Regarding the technological component, photovoltaic energy seems the most favorable due to its low environmental impact and the considerable reduction in prices experienced by the solar panel market in recent years.